PERK Signaling Controls Myoblast Differentiation by Regulating MicroRNA Networks - Tan, Ye-Ya; Zhang, Yin; Li, Bin; Ou, Yang-Wen; Xie, Shu-Juan; Chen, Pei-Pei; Mei, Shi-Qiang; Huang, Qiao-Juan; Zheng, Ling-Ling; Qu, Liang-Hu (Frontiers in Cell and Developmental Biology, 2021)
The unfolded protein response (UPR) plays important roles in various cells that have a high demand for protein folding, which involved in the process of cell differentiation and development. Here, we separately knocked down the three sensors of the UPR in myoblasts and found that PERK knockdown led to a marked transformation in myoblasts from a fusiform to a rounded morphology, which suggests that PERK is required for early myoblast differentiation. Interestingly, knocking down PERK induced reprogramming of C2C12 myoblasts into stem-like cells by altering the miRNA networks associated with differentiation and stemness maintenance, and the PERK-ATF4 signalling pathway transactivated muscle differentiation-associated miRNAs in the early stage of myoblast differentiation. Furthermore, we identified Ppp1cc as a direct target gene of miR-128 regulated by the PERK signalling pathway and showed that its repression is critical for a feedback loop that regulates the activity of UPR-associated signalling pathways, leading to cell migration, cell fusion, endoplasmic reticulum expansion, and myotube formation during myoblast differentiation. Subsequently, we found that the RNA binding protein ARPP21, encoded by the host gene of miR-128-2, antagonized miR-128 activity by competing with it for binding to the 3’ untranslated region (UTR) of Ppp1cc to maintain the balance of the differentiation state. Together, these results reveal the crucial role of PERK signalling in myoblast maintenance and differentiation and identify the mechanism underlying the role of UPR signalling as a major regulator of miRNA networks during early differentiation of myoblasts.